"Like, What Else Could Go Wrong?" Multiple Contextual Stressors in Food Insecure Households. Issue 4 (7th June 2021) - Sensoy Bahar, Ozge; Ali, Samira; Iwaki, Tomoko J.; Dean-Assael, Kara; Arias, Diana M.; Jones, Jayson K.; Whorten Lang, Victoria; Latorre, Maria Cristina; McKay, Mary
ABSTRACT: Food insecurity is often considered in isolation from other stressors, limiting our contextual understanding of individual or familial experiences. Hence, this study examined families in their unique contexts, recognizing the myriad of hardships they experienced. Informed by the cumulative risk framework, in-depth interviews were conducted with 59 caregivers recruited from food pantries in New York. Analytic induction techniques were used for data analysis. In addition to food insecurity, limited income and unemployment, mental health, physical health, and public assistance were identified. Most participants experienced multiple stressors concurrently. These findings have implications for developing interventions grounded in families' experiences and needs.